2022
DOI: 10.21315/tlsr2022.33.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Stingless Bees Pollination Increases Fruit Formation of Strawberry (Fragaria x annanassa Duch) and Melon (Cucumis melo L.)

Abstract: Stingless bees (Apidae: Meliponini) are distributed in tropical and subtropical areas in the world. Stingless bees are potential pollinator to increase yield of various crops species. We measured the pollination effectiveness of stingless bees, i.e., Tetragonula laeviceps in strawberry (Fragaria x annanassa) and Heterotrigona itama in melon (Cucumis melo) in the greenhouse. Pollination effectiveness of stingless bees were measured based on their visiting activities, i.e., foraging rate and flower handling time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, the highest foraging activity in Tetragonula pagdeni was at 10:00 in greenhouse conditions ( Wongsa, Duangphakdee & Rattanawannee, 2023 ). Furthermore, several studies reported that at 11:00, T. laeviceps was the visiting mostly strawberry, mango, and orange flowers ( Atmowidi et al, 2022 ; Chuttong et al, 2022 ; Nurdiansyah, Abduh & Permana, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the highest foraging activity in Tetragonula pagdeni was at 10:00 in greenhouse conditions ( Wongsa, Duangphakdee & Rattanawannee, 2023 ). Furthermore, several studies reported that at 11:00, T. laeviceps was the visiting mostly strawberry, mango, and orange flowers ( Atmowidi et al, 2022 ; Chuttong et al, 2022 ; Nurdiansyah, Abduh & Permana, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This issue has prompted several studies on applied bee cultivation in agroecosystems to enhance productivity ( Aslan & Yavuksuz, 2010 ; Nunes-Silva et al, 2013 ; Hall et al, 2020 ; Amon et al, 2023 ). The application of meliponiculture has expanded in tropical regions with enhanced pollination efficacy of 10–70% ( da Silva et al, 2017 ; Azmi et al, 2019 ; Layek, Das & Karmakar, 2022 ; Reddy, Chauhan & Singh, 2022 ; Balaji et al, 2023 ; Wongsa, Duangphakdee & Rattanawannee, 2023 ), particularly in Indonesia with 20–48% ( Putra, Permana & Kinasih, 2014 ; Alpionita, Atmowidi & Kahono, 2021 ; Atmowidi et al, 2022 ; Nurdiansyah, Abduh & Permana, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are eusocial insects (Chakuya et al, 2022) belonging to the family Apidae and subfamily Meliponinae. They forage on nectar and pollen enhancing pollination of more than 60% of different commercial crops (Heard, 1999, Atmowidi et al, 2022Ramalho, 2004). Stingless bees have specialized structures called corbicula on their legs (Asiko, 2012) which enable them to e ciently gather and carry pollen.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, the stingless bee Tetragonula iridipennis was found to be a successful pollinator in cucumber greenhouses ( Mitta et al, 2017 ). Atmowidi et al (2022) investigated the pollination effectiveness of stingless bees of two genera, Tetragonula in strawberry and Heterotrigona in melon, in a greenhouse. Tetragonula increased the number of fruits and quality of strawberries, and Heterotrigona did the same for melons.…”
Section: Introductionmentioning
confidence: 99%